2020
DOI: 10.1177/1464420720958015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of core lattice topology on the properties of sandwich panels produced by additive manufacturing

Abstract: Sandwich structures are frequently used in automotive, aerospace and marine industries, as they provide adequate functional properties. The two-dimensional regular hexagonal cell shape, i.e. honeycomb is the most used core structure in sandwich panels. Recently, a new type of cellular structures composed of lattice struts has been proposed, as they combine high stiffness, strength and energy absorption with low weight. The main purpose of this research is to investigate the effect of the lattice topology on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…2,[12][13][14][15][16] Truss or lattice cores have received considerable attention because, in comparison with the honeycomb, they may exhibit superior buckling resistance, at low relative density. 13,16,17 Intensive research was carried out by several researchers to study the mechanical behavior of cellular materials or of honeycomb sandwich panels under different loading conditions. 2,10,11,13,[18][19][20][21][22][23] The most widely studied and used core is the conventional honeycomb made by the repetition of equal hexagonal cells.…”
Section: Introductionmentioning
confidence: 99%
“…2,[12][13][14][15][16] Truss or lattice cores have received considerable attention because, in comparison with the honeycomb, they may exhibit superior buckling resistance, at low relative density. 13,16,17 Intensive research was carried out by several researchers to study the mechanical behavior of cellular materials or of honeycomb sandwich panels under different loading conditions. 2,10,11,13,[18][19][20][21][22][23] The most widely studied and used core is the conventional honeycomb made by the repetition of equal hexagonal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The results of FEA, theoretical and experiments are compared as shown in Figure 21, revealed that the elastic FEA results showed the lower flexural deformation of the sandwich panel concerning the experimental results 78,79 knowing the FEA based on elastic analysis and that perfect bonding between the layers are assumed. It is obvious that experimental results demonstrated higher deformation than the FEA due to the interfacial adhesion incompatibility between dissimilar printed layers in addition to the delay occurred during printing the second material printing sequence.…”
Section: Resultsmentioning
confidence: 92%
“…A lot of research has been done on the performance of different types of cores and various classifications have been presented by researchers. Figure 3 shows the main types of sandwich cores: foam [19,20], z-pinned [21], corrugated [22,23], lattice [24,25], balsa [26,27], cork [28,29], and composite [30,31].
Figure 3.Classification for sandwich cores.
…”
Section: Sandwich Structuresmentioning
confidence: 99%